Can Transformational Leadership Retain Employee through The Role of Job Satisfaction as a Mediative at The Sunan Drajat Lamongan Boarding School Business Unit? - Prasetyo, Ari (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
This study highlights the strategic significance of Islamic boarding schools as historic contributors to Islam's development in Indonesia. The pivotal role these schools play in community empowerment is realized through their business units. The research aims to analyze the influence of transformational leadership on turnover intention, mediated by job satisfaction, in the business unit of Sunan Drajat Lamongan Islamic boarding school. Employing an explanatory research method, the study utilizes transformational leadership as the independent variable, job satisfaction as the intervening variable, and turnover intention as the dependent variable. Data is collected through questionnaires and analyzed using Structural Equation Modeling (SEM) processed with SmartPLS. The findings indicate that transformational leadership significantly positively impacts job satisfaction, while job satisfaction significantly negatively influences turnover intention. However, transformational leadership alone has an insignificantly negative effect on turnover intention. Job satisfaction acts as a mediating factor in the influence of transformational leadership in preventing turnover intention. However, transformational leadership without job satisfaction, fails to prevent employee turnover intention. In this context, Islamic boarding schools can optimize transformational leadership and job satisfaction strategies to minimize employee turnover intention, thereby enhancing employee performance and contributing to community empowerment